Design and Development of a Himalayan Studies Information System for India: A Proposed Model - Singh, Anil (Information Technology and Libraries, 2005)
The ever-increasing need for information,with its complexity and escalating costs; theenormous growth in publications, and theemergence of subject specialization have compelled librarians to share resources throughinformation networks and systems. Thispaper describes the necessity of networkingamong the Himalayan Studies and ResearchCenters in India, allowing the sharing ofinformation originating from the HimalayanStudies Information System (HIMIS). Thepaper also discusses in brief the definition ofinformation systems, as well as the objectivesand needs of a proposed HIMIS.